PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP HASIL BELAJAR IPA BIOLOGI SISWA KELAS XI SMA NEGERI 2 TOMA TAHUN PEMBELAJARAN 2022/2023 - Hulu, Meldasari (Universitas Nias Raya, 2024)
This research uses a type of quantitative research, namely the experimental class uses the Quantum Learning model and the control class XI IPA-1 SMA Negeri 2 Toma while the population in the control class was class XI IPA-2 SMA Negeri 2 Toma. the results of the research stated that in the experimental class by carrying out a pretest the average lerarning outcome was 37.81 and the posttest obtained an average learning outcome of 68.12. Meanwhile, in the control class, the the pretest obtained an average learning outcome of 41.5 and the posttest obtained an average learning outcome of 73. So, the Quantum Learning learning model has more influence on learning outcomes compared to conventional learning models. The conclusion of the research based on hypothesis test conclutations is that tcount = 0.2906 is greater than table = 0.1437 with a significance of 5% because tcount in table means Ha is accepted and Ho is rejected, which means there is an influence or the Quantum Learning learning model. With the existence or the Quantum Learning learning model for Biology Science learning outcomes, it is hoped that every subject teacher will apply this learning model to improve students’ learning abilities and can improve the way each student learns and become a guide or reference for every reader or researcher who wants to write the next thesis.